1974
DOI: 10.1021/jo00927a057
|View full text |Cite
|
Sign up to set email alerts
|

Melanin. I. Kinetics of the oxidative cyclization of dopa to dopaquinone

Abstract: 96, 1256 (1974).(2) (a) For a recent review of alkaloids based on these ring systems, see J. E. Saxton in the "Alkaloids," Vol. 2, Specialist Periodical Reports of the Chemical Society, London, 1972. (b) For recent synthetic methods in the pyrrolizidine series, see N.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
68
0

Year Published

1974
1974
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(70 citation statements)
references
References 0 publications
2
68
0
Order By: Relevance
“…In addition, Adams (4,5) has shown that p-benzoquinones with electronwithdrawing substituents can be nucleophilically attacked by water to yield a trihydroxy compound, which can be further oxidized to the hydroxyquinone. Several other workers (6)(7)(8)(9) have investigated the reactions of o-quinones from Dopa, catechol, and 4-methyl catechol in aqueous solutions, but the emphasis has been mostly on acidic solutions and at low concentrations, which significantly suppress the coupling reaction. Outside of the work by Stum and Suslov (10), there has been little electrochemical work done on the coupling reactions of quinones.…”
mentioning
confidence: 99%
“…In addition, Adams (4,5) has shown that p-benzoquinones with electronwithdrawing substituents can be nucleophilically attacked by water to yield a trihydroxy compound, which can be further oxidized to the hydroxyquinone. Several other workers (6)(7)(8)(9) have investigated the reactions of o-quinones from Dopa, catechol, and 4-methyl catechol in aqueous solutions, but the emphasis has been mostly on acidic solutions and at low concentrations, which significantly suppress the coupling reaction. Outside of the work by Stum and Suslov (10), there has been little electrochemical work done on the coupling reactions of quinones.…”
mentioning
confidence: 99%
“…A peak current ratio (I p C1 /I p A1 ) of nearly unity, particularly during the repetitive cycling of potentials may be considered as a criterion for the stability of p-quinone produced at the surface of the electrode under experimental condition. In other words, any hydroxylation [17][18][19][20][21][22] or dimerization [23][24][25] reaction is too slow to be observed on the cyclic voltammetry time-scale.…”
Section: Resultsmentioning
confidence: 99%
“…15,16,17 These studies provided the first order rate constants for the cyclisation of the free amines (k 2 , Scheme 3) as well as the overall rate constants for aminochrome formation (k f , Table 2 Scheme 3) is the rate limiting process. Subsequently, a combined theoretical and kinetic study of the oxidation of L-dopa using mushroom tyrosinase under acidic conditions (pH 5.0-6.0) was able to derive values of the rate constants for both the first order deprotonation step (k 1 ) and the cyclisation step (k 2 )(Scheme 3).…”
Section: Methodsmentioning
confidence: 99%